PENGGELOLAAN SAMPAH RUMAH TANGGA DI PESISIR DESA LAUT BIRU DAMPAK SAMPAH TERHADAP EKOSISTEM LAUT - Arman, Veggy; Kasim, Faizal; Pasisingi, Nur Alim; Kalaka, Sri Rahayu; Lantu, Iin Susilawati; Ahmad, Indra G (Jurnal Abdi Insani, 2024)
Laut Biru Village is a village located in Bone Raya District, Bone Bolango Regency. The area of this village is 2.64 km2 with a percentage of the sub-district area of 4.12%. The population of Laut Biru Village is 711 thousand people or 1.79% of the total population in Bone Raya District. The occupations of some people are farmers and fishermen. In the context of development and community independence, Laut Biru Village adheres to the Together We Advance concept or a concept where the community voluntarily works together to achieve goals without depending on assistance from the government or other institutions. The aim of this activity is to help local communities gain knowledge and skills in utilizing the resources they have to improve welfare through waste management and contribute to maintaining the sustainability of the marine environment and coastal ecosystems. The method used is the individual mentoring method by providing training and mentoring which is equipped with learning by doing techniques (learning while working). The Thematic Real Work Lecture Program in Laut Biru Village lasts for 45 days. Program activities begin with the initial stage of direct observation in coastal areas. The core program focuses on increasing the self-sufficiency of seaside community reserves by addressing the impact of waste on marine ecosystems and encouraging household waste management. The program's core activities include outreach to increase awareness about the dangers of waste and the importance of utilizing existing resources. Implementation of the core program activities for Gorontalo State University KKN-T students in Laut Biru Village began with providing outreach on the Dangers of the Impact of Waste on Marine Ecosystems and Management of Household Waste on the Coast of Lau Biru Village by presenters from Gorontalo State University Lecturers and the lets clean our ocean program namely social service activities carried out along the coast of Laut Biru Village which involve all elements of society and the government of Laut Biru Village. The collected waste is then processed into paving blocks. Garbage is the biggest problem in Laut Biru Village. Because there is no TPA (Final Disposal Site) so people throw their rubbish on the edge of the beach. Therefore, follow-up action is needed regarding waste so that it does not spread and damage the environment and marine ecosystem.